2015
DOI: 10.4317/medoral.20714
|View full text |Cite
|
Sign up to set email alerts
|

Association between general and oral health-related quality of life in patients treated for oral cancer

Abstract: BackgroundLess is known about the association between general health-related quality of life (HRQoL) and oral HRQoL (OHRQoL) among patients with specific diseases. The aim of this study was to assess the association between patient-centered outcome measurements (HRQoL and OHRQoL) of oral cancer patients at least 6 months after treatment.Material and MethodsHRQoL was measured with the 12-Item Short Form Health Survey (SF-12); OHRQoL was evaluated using the Oral Health Impact Profile (OHIP-14) and the Oral Impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…A study from Germany also reported significant correlation between OHRQOL and HRQOL in both physical and mental component scores [31]. Similar findings were reported by a study among patients with oral and oropharyngeal cancer patients which reported significant association of OHIP-14 scores in all domains of HRQOL assessed through SF-12 [32]. A Korean study also concluded that selfrating general health was positively associated with oral health [33].…”
Section: Correlation Between Ohrqol and Hrqolsupporting
confidence: 76%
“…A study from Germany also reported significant correlation between OHRQOL and HRQOL in both physical and mental component scores [31]. Similar findings were reported by a study among patients with oral and oropharyngeal cancer patients which reported significant association of OHIP-14 scores in all domains of HRQOL assessed through SF-12 [32]. A Korean study also concluded that selfrating general health was positively associated with oral health [33].…”
Section: Correlation Between Ohrqol and Hrqolsupporting
confidence: 76%
“…The RAND SF-36 has a lack of disease-specific items; therefore, our study shows the advantage of combining the generic questionnaire on general health, the RAND SF-36, already utilized in EB populations (Tabolli et al, 2009), with the specific one related to the oral health, the OHIP-49, that has been validated and reliable in other oral-pharyngeal diseases (Lopez-Jornet et al, 2010;Barrios et al, 2015;Rimal et al, 2015), but has never been tested in patients with EB. The use of a generic and specific quality of life instrument has been suggested as the best option to better address the ongoing debate about whether generic or disease-specific instruments should be used (Streiner & Norman, 2003).…”
Section: Discussionmentioning
confidence: 90%
“…In general, HRQoL and OHRQoL are closely related in generally healthy individuals, where OHRQoL can be seen as a subaspect of the whole HRQoL [ 35 ]. However, specific diseases might affect this relationship to an unclear extent [ 36 ]. Furthermore, HRQoL can also be directly associated with oral health conditions [ 6 ].…”
Section: Discussionmentioning
confidence: 99%